Neurotoxicity and mode of action of N, N-diethyl-meta-toluamide (DEET). - Daniel R Swale (PLoS ONE, 2014)
Recent studies suggest that N, N-diethyl-meta-toluamide (DEET) is an acetylcholinesterase inhibitor and that this action may result in neurotoxicity and pose a risk to humans from its use as an insect repellent. We investigated the mode of action of DEET neurotoxicity in order to define the specific neuronal targets related to its acute toxicity in insects and mammals. Although toxic to mosquitoes (LD50 ca. 1.5 µg/mg), DEET was a poor acetylcholinesterase inhibitor (<10% inhibition), even at a concentration of 10 mM. IC50 values for DEET against Drosophila melanogaster, Musca domestica, and human acetylcholinesterases were 6-12 mM. Neurophysiological recordings showed that DEET had excitatory effects on the housefly larval central nervous system (EC50: 120 µM), but was over 300-fold less potent than propoxur, a standard anticholinesterase insecticide. Phentolamine, an octopamine receptor antagonist, completely blocked the central neuroexcitation by DEET and octopamine, but was essentially ineffective against hyperexcitation by propoxur and 4-aminopyridine, a potassium channel blocker. DEET was found to illuminate the firefly light organ, a tissue utilizing octopamine as the principal neurotransmitter. Additionally, DEET was shown to increase internal free calcium via the octopamine receptors of Sf21 cells, an effect blocked by phentolamine. DEET also blocked Na(+) and K(+) channels in patch clamped rat cortical neurons, with IC50 values in the micromolar range. These findings suggest DEET is likely targeting octopaminergic synapses to induce neuroexcitation and toxicity in insects, while acetylcholinesterase in both insects and mammals has low (mM) sensitivity to DEET. The ion channel blocking action of DEET in neurons may contribute to the numbness experienced after inadvertent application to the lips or mouth of humans.